2021
DOI: 10.1007/s10461-021-03545-w
|View full text |Cite
|
Sign up to set email alerts
|

PrEParing for NextGen: Cognitive Interviews to Improve Next Generation PrEP Modality Descriptions for Young Men Who have Sex with Men

Abstract: Next generation PrEP formulations may circumvent factors that impede daily oral pre-exposure prophylaxis (PrEP) use among young men who have sex with men (YMSM). We conducted video-based cognitive interviews with 20 YMSM (age 16-24) recruited in the US Northeast to assess participants' attitudes and comprehension of written descriptions of next generation PrEP modalities. Participants were predominately racial/ethnic minorities and half used daily oral PrEP. We identified four main areas for improvement of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Familiarity with next‐generation products was not measured. Although we used descriptions of the products developed and tested in cognitive interviews with YMSM [ 34 ], preferences may differ if or when the products are available. Lastly, the conjoint experiments were designed to examine preferred features and willingness to pay for product features; however, because each participant was randomized to review one product, we could not quantitatively compare feature preferences across products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Familiarity with next‐generation products was not measured. Although we used descriptions of the products developed and tested in cognitive interviews with YMSM [ 34 ], preferences may differ if or when the products are available. Lastly, the conjoint experiments were designed to examine preferred features and willingness to pay for product features; however, because each participant was randomized to review one product, we could not quantitatively compare feature preferences across products.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions of PrEP products and images for the product features were reviewed by participants prior to the conjoint experiment. Definitions and images were developed through cognitive interviews with YMSM (reported previously [ 34 ]). Given that many of the products are still under development, and that we were trying to assess optimal attributes, we did not include the frequency of recommended use in the descriptions (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…These were issues touched upon by participants but could not be expanded upon enough to reach thematic saturation. Several studies have suggested that there is no single preference that reflects the needs of all individuals in given community; therefore, future research and interventions should provide education about the diversity of all PrEP technologies to promote informed decision-making for YMSM of color (Bauermeister et al, 2020; Biello et al, 2022; Biello, Valente, et al, 2018; Martinez et al, 2022). Targeted rollout of LAI PrEP must include careful education for clients about clinician-administered injections, as well as risk mitigation strategies for missed doses so that this PrEP innovation actually benefits those who need it.…”
Section: Discussionmentioning
confidence: 99%
“…attributes; e.g. 50% effective; 80% effective; 95% effective) that may affect intended users' uptake of these products [7,21]. This manuscript describes MTN-035 participants' choice trade-offs after having the opportunity to use each of three rectal placebo modalities (i.e.…”
Section: Introductionmentioning
confidence: 99%